Kajian Tingkat Kerentanan Sosial Terhadap Masyarakat Terdampak Bencana di Kecamatan Trienggadeng Pasca Gempa Bumi Pidie Jaya 2016 - Rinaldy Maulidin*; Indra Indra; Yusya Abubakar (Universitas Syiah Kuala, 2022)
A disaster often causes survivors to be in a more vulnerable position than before. In the 2016 Pidie Jaya earthquake, five villages experienced a directed impact from the disaster. This study aims to determine the level of social vulnerability and to analyze the dynamics of changes in social vulnerability at the Trienggadeng District level, Pidie Jaya Regency in the period 2015-2021. This research uses descriptive quantitative method. The data used in this study include secondary data and primary data. Respondents in this study amounted to 98 people from communities in five villages in Trienggadeng District. The results of secondary data study show that the value of social vulnerability in the period 2015-2021 which consists of aspects of population density, sex ratio, vulnerable age, poor population, and vulnerability is in the range (54.38-267.71) where Tampui Village into the high class category with a value of (267.71). Meanwhile four other villages fall into the low class category, such as: Kuta Pangwa Village (54.38), Meucat Pangwa (71.09), Mee Pangwa (84.03) and Deah Teumanah (99.95). The aspects identified as triggers for social vulnerability in this study include: poverty rates in Mee Pangwa and Deah Teumanah Villages, solid waste management in all study villages, and population density in Tampui Village. Furthermore, an analysis of primary data shows that there has been an increase in quality and quantity in aspects of sanitation and access to health in the period 2016-2021.